2009
DOI: 10.1002/clen.200900050
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Flame Retardants and Plasticizers in Rain and Snow from Middle Germany

Abstract: The role of precipitation as an important source of, and entry pathway for, organophosphates (OPs) into the aquatic environment was investigated. Rainwater and snow samples (53 and 43, respectively) collected between November 2007 and April 2008 from urban and remote areas of middle Germany were analyzed for OPs by gas chromatography-mass spectrometry (GC-MS) after solid phase extraction (SPE). The analytes tris(2-chloroethyl) phosphate (TCEP), tris(2-chloro-1-methylethyl) phosphate (TCPP), tris(1,3-dichloro-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 29 publications
6
54
3
Order By: Relevance
“…This result disagreed with previous study showing no significant seasonal trends for the OPEs in urban lake water samples from Germany (Regnery and Puttmann, 2010). It has been previously demonstrated that the proportions of OPEs in condensate and internal vehicle air reveal an increase when the temperature is increased (Regnery and Püttmann, 2009). The average temperature is about 30 C in July and August (summer) in Beijing, while it is only about 10 C and 5 C in November and February (winter), respectively.…”
Section: Seasonal Variationcontrasting
confidence: 99%
See 2 more Smart Citations
“…This result disagreed with previous study showing no significant seasonal trends for the OPEs in urban lake water samples from Germany (Regnery and Puttmann, 2010). It has been previously demonstrated that the proportions of OPEs in condensate and internal vehicle air reveal an increase when the temperature is increased (Regnery and Püttmann, 2009). The average temperature is about 30 C in July and August (summer) in Beijing, while it is only about 10 C and 5 C in November and February (winter), respectively.…”
Section: Seasonal Variationcontrasting
confidence: 99%
“…The occurrence and fate of OPEs in aquatic environment is of concern since these compounds can massively reach surface water from industrial and domestic sewage discharge (Fries and Puttmann, 2003;Martinez-Carballo et al, 2007) and atmosphere deposition (Bacaloni et al, 2008;M€ oller et al, 2011;Regnery and Püttmann, 2009). The discharge of industrial and domestic sewage is considered as the major source of OPEs in surface water (Reemtsma et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 This can be explained by the shorter atmospheric half-life of TCPP (the calculated half-lives for the atmospheric reaction with hydroxyl radicals are 8.6 h for TCPP and 17.5 h for TCEP) or by the higher potential of TCPP to adsorb to airborne particles, which may then be removed through dry and wet deposition during long-range transport. 51 Among the chlorinated OPFRs, the range of TDCPP concentrations across all the cities was 2.1−280 pg/m 3 (39 ± 38 pg/m 3 , n = 149) in the PM 2.5 samples, which was much lower than the corresponding values for TCPP and TCEP. Most studies in the indoor environment have shown the dominance of different compounds (TCPP, TCEP, or TDCPP) due to different types, amounts, and ages of flame retardant-treated products within these environments.…”
Section: Resultsmentioning
confidence: 94%
“…Widespread use of these flame retardants has led to their accumulation in various environments at concentrations ranging from nanograms to several micrograms per liter (1)(2)(3)(4)(5). Although these compounds are considerably less toxic than organophosphorus pesticides and chemical warfare agents, many studies have shown their diverse toxic effects (6).…”
mentioning
confidence: 99%